Using Local Ecological Knowledge (LEK) to inform the multi-habitat life cycle of wreckfish: A Ligurian Sea case study for Mediterranean conservation - DESIDERÀ, ELENA; DI BLASI, DAVIDE; POLI, FEDERICA; WILLIS, TREVOR J.; BAVA , SIMONE; GUIDETTI, PAOLO (Mediterranean Marine Science, 2025)
Local Ecological Knowledge (LEK) from fishers and sea users is invaluable for reconstructing the occurrences of data deficient and vulnerable fish species, particularly target species. This study explores the distribution patterns of the data-deficient wreckfish Polyprion americanus in the Ligurian Sea (NW Mediterranean Sea) using semi-structured interviews with 40 sea users (27 fishers and 13 observational data providers). We identified key habitats associated with five main size classes of wreckfish, from surface waters to 1000 m depth, including vulnerable ecosystems like seamounts and cold-water coral habitats. Smaller individuals (0-1.5 kg) were mainly found in pelagic habitats, frequently near floating objects, while larger individuals (>3 kg) were common in slope and seamount habitats. Abundance declines across all size classes were attributed to overfishing and, according to some respondents, a reduction in floating debris may have specifically affected the presence of smaller individuals. Fishing techniques varied by size class, with technological advances notably impacting larger individuals near seamounts. The study supports LEK as a valuable complementary information source to conventional research, advocating for updated conservation measures, including revised size limits and enhanced protection of vulnerable habitats.